Natural compound Alternol actives multiple endoplasmic reticulum stress-responding pathways contributing to cell death - Liu, Wang; He, Chenchen; Li, Changlin; Ye, Shazhou; Zhao, Jiang; Zhu, Cunle; Wang, Xiangwei; Ma, Qi; Li, Benyi (Frontiers in Pharmacology, 2024)
Alternol is a small molecule isolated from the fermentation of a mutant fungus obtained from Taxus brevifolia bark. Our previous studies showed that Alternol treatment induced reactive oxygen species (ROS)-dependent immunogenic cell death. In this study, a comprehensive investigation was conducted to explore the mechanisms involved in Alternol-induced immunogenic cell death. Our results showed that Alternol interacted with multiple cellular chaperone proteins and increased their expression levels, including endoplasmic reticulum (ER) chaperone hypoxia up-regulated 1 (HYOU1) and heat shock protein 90 alpha family class B member 1 (HSP90AB1), as well as cytosolic chaperone heat shock protein family A member 8 (HSPA8). These data indicated a potential mechanistic cause of unfolded protein response (UPR) after Alternol treatment. Further investigation revealed that Alternol treatment triggered ROS-dependent ER stress responses via protein kinase R-like ER kinase (PERK), inositol-requiring enzyme 1 (IRE1), and the double-stranded RNA-dependent protein kinase (PKR) but not activating transcription factor 6 (ATF6) cascades, leading to ATF-3/ATF-4 activation, C/EBP-homologous protein (CHOP) overexpression, and X-box binding protein XBP1 splicing induction. In addition, inhibition of these ER stress cascades blunted Alternol-induced extracellular adenosine triphosphate (ATP) release, one of the classical hallmarks of immunogenic cell death. Taken together, our data demonstrate that Alternol treatment triggered multiple ER stress cascades, potentially leading to immunogenic cell death.